(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
A summary of the article’s objectives, significance of the problem, and conclusions. For example: "coronary heart disease (CHD) in combination with moderate mitral insufficiency is a complex clinical task that requires a comprehensive approach. The article presents modern strategies of surgical and conservative treatment aimed at improving the prognosis and quality of life of patients."